Diagnosis and Treatment of Male Accessory Breast Cancer: A Comprehensive Systematic Review - Pang, Liwei; Cui, Meiying; Dai, Wanlin; Wu, Shuodong; Kong, Jing (Frontiers in Oncology, 2021)
Background Accessory breast cancer is extremely rare, especially in male patients, and only a few cases have been reported in the literature. To date, no specific guidelines regarding its diagnosis and treatment are available. Objectives This study aimed to investigate the guidelines for the diagnosis and treatment of male accessory breast cancer by reviewing the available literature on this disease. Methods The Web of Science, Cochrane, PubMed, and CNKI databases were systematically searched (last search: 30 November 2020) to identify studies on male axillary accessory breast cancer. The following data were extracted: author names, number of patients, country, patient age, tumour location, tumour size, pathologic diagnosis, and treatment. Results There were 16 studies included (6 in Chinese and 10 in English), corresponding to 16 cases of male axillary accessory breast cancer. Primary surgical resection is currently the main procedure, followed by comprehensive treatment including chemotherapy, radiotherapy, and endocrine therapy. Patient age ranged from 51–87 years, and the average age was 67.1 years. The main clinical features of the patients were pain, the portion of the skin covering the mass was either reddish or purplish, and the mass could show swelling and erosion on the surface, with purulent exudate. Conclusions Once male accessory breast cancer is diagnosed, we can follow the latest guidelines for the diagnosis and treatment of breast cancer. Tumour biopsy and resection seems the treatment of first choice, combined with comprehensive treatment including chemotherapy, radiotherapy, and endocrine therapy.